Store Image’s Influence on Perceived Quality of Store Brands and Store Brand Purchasing Behavior - Gültekin, Beyza; Özer, Leyla (Richtmann Publishing, 2012)
In the marketing literature store image and its dimensions are identified and studied by many researchers. However, itsinfluence on consumersâ€™ â€œstore brand purchaseâ€ and its â€œperceived qualityâ€ is rarely studied for different product categories (food, nonfood).In this framework, the purpose of this study is to examine store image and its influence on the consumersâ€™ store brand choice andperceived quality of store brands. Store image dimensionsâ€™ effect on each mentioned variable is tested on a sample of 378 customerswho usually shop from hypermarkets in Ankara, Turkey. As there are too many store image variables, initially factor analysis is appliedto group the store image variables in order to reduce the number of variables to a smaller set of independent factors. In the second step,â€œstore image dimensions and store brand purchaseâ€ and â€œstore image dimensions and perceived quality of store brandsâ€ are investigatedwith the Regression Analysis. ANOVA was applied to identify the variances between perceived quality of food and non-food categories.It was found that store atmosphere dimension of store image affects perceived quality of store brands. Perceived quality of store brandsaffects the purchasing of store brands whereas any of the store image dimensions does not. In food and non-food categories perceivedquality of store brands effect store brand purchasing. In non-food category, store atmosphere dimension of store image affects perceivedquality of these products.